CPEC – A Flagship of New Silk Road: Perceptions of ‘Sinophilia’ and ‘Sinophobia’ in Pakistan* - Syed Raghab Ali; Ishtiaq Ahmed Chaudhri (Journal of Political Studies, 2018)
The present research explores the perceptions of opinion leaders of Pakistan about Sinophilia and Sinophobia under regional dynamics of New Silk Road (NSR) within the contexts of Regional Integration and Regional Security Complex Theory for political, social and security aspects of CPEC. A survey from 400 opinion leaders; Educationists, Journalists, Bureaucrats and Security Personnel, in Lahore, Capital City of Punjab, Pakistan was conducted to detect the perceptions. Existing knowledge about the project (IV), demographics of respondents were measured. Positive political impact on Pakistan and China, Positive and Negative social impacts of CPEC on Pakistan (MO), and Positive impacts of CPEC on Pakistan and China were tested. ANOVA and Linear Regression Analysis were applied. PLS-SEM was also applied to test the proposed model. The study found the influential impacts of existing knowledge, political and social impacts on security matters related to CPEC for both Pakistan and China under NSR.